Al-Sunnah Al-Nabawiyyah Wa-Dauruha Al-Ihkamiyyah fi istinbat Al-Ahkam Al-Shar'IYYAH - A. S. Elfarese, Samira (2014)
This research is entitled Sunnah and its role in devising the legal provisions. The significance of this research is that there is not much difference between the methodology Quran and Sunnah in terms of inference with them. Retrieving from Qur'an alone is not enough; hence it can be complemented with Sunnah as the prophetic verses are originally from the assets of Islamic law and cannot be dispensed with in any way. The aim of the research is to identify the Sunnah of the Prophet Muhammad, the types and importance. This is to rebut claims that the Quran is enough and there is no need for the Sunnah. This research aims to provide concrete facts and studies on God, divinity and oneness and its provisions recognizing and obedience, and attempt producing the best way to educate the Sunnah of the Islamic nation. The research consists of an introduction and three chapters. The objectives and past studies are also included. The research methodology adopted in this research is an analytical inductive approach for what has been mentioned on this subject in the literature of jurisprudence book that relies on relevant religious texts and discuss their implications. The researcher has pointed out that Muslims and their scholars are unanimously from the first generation up to the present day on the necessity of Sunnah. And they continued using it as avidence witout any doubt, Sunnah is one of the obligatory evidence in shariyyah that must be practiced if it’s true, as well as the Quran.